2018
DOI: 10.5455/medarh.2018.72.125-130
|View full text |Cite
|
Sign up to set email alerts
|

Embitterment in War Veterans with Posttraumatic Stress Disorder

Abstract: AimThe aim of this study was to analyze frequency of embitterment in war veterans with Posttraumatic stress disorder (PTSD).Patients and MethodsIt was analyzed 174 subjects (from Health Center Zivinice/ Mental Health Center) through a survey conducted in the period from March 2015 to June 2016, of witch 87 war veterans with PTSD and control subjects 87 war veterans without PTSD. The primary outcome measure was the Post-Traumatic Embitterment Disorder Self-Rating Scale (PTED Scale) who contains 19 items designe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PRISMA flowchart delineates the review process (see figure 1). Of the 81 full texts included in the review,6 12–21 43–112 some reported multiple studies in the same paper, so there were 88 separate studies included in the review. Of these, six reported prevalence estimates or average scores that could not be pooled, so they were included in the narrative synthesis only.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that PTED often occurs at work, for instance, 73% of PTED patients reported the triggering event as work-related 11. PTED is evident in occupations such as the armed forces,12 13 educators,14 15 healthcare professionals,9 16 17 the unemployed18 19 and in a mix of occupations 20 21…”
Section: Introductionmentioning
confidence: 99%
“…127 SABIC company announced the production of bio-ethylene. 128 The first commercial bio-based ethylene-propylene diene monomer is made of 70% of bio-based ethylene and propylene 129 .…”
Section: Bio-based Conventional Synthetic Rubbersmentioning
confidence: 99%
“…In the general population, people with PTED have a higher severity of perceived stress and depressive symptoms [ 7 ]. A recent study of war veterans found that those with PTSD had more symptoms of PTED [ 8 ]. In a study that examined comorbid mental disorders and psychometric characteristics of PTED, participants with PTED displayed significantly higher levels of depression, anxiety, somatization, PTSD, and obsessive-compulsive symptoms [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia has been proposed as an additional symptom of PTED [ 1 ], but no studies have explored the association between PTED symptoms and insomnia. Most research on the association between PTED and major psychopathology has been done in adult populations before old age [ 6 - 8 , 10 - 14 ]. The clinical presentation of psychiatric disorders in old age often differs from that in younger age [ 15 - 18 ].…”
Section: Introductionmentioning
confidence: 99%